PEMBERDAYAAN MASYARAKAT MELALUI KEWIRAUSAHAAN DAN GREEN ECONOMY DI KELURAHAN KARYA JAYA II KECAMATAN KERTAPATI KOTA PALEMBANG - Novi Yarsah, Waldi; Pratama Atiyatna, Dirta; Hamidi, Ichsan; Mahdi Igamo, Alghifari (Fakultas Pertanian, 2024)
The benefits of entrepreneurial activities include creating jobs, reducing unemployment, improving living standards and community income, encouraging innovation and independence, and encouraging economic growth and national competitiveness. The concept of green economy has brought about a change in the development paradigm in developed and developing countries. This activity aims to develop the ability of the community, especially housewives in the field of entrepreneurship and to increase the knowledge of housewives in supporting environmental sustainability to increase community economic independence through the green economy. The training was conducted through a participatory approach with the methods of counseling, material delivery, and discussion and question and answer. There were 25 participants who attended, including the local village head and his apparatus as well as the community who belonged to MSME players, especially housewives at the Karya Jaya II Village Hall. This training provides an overview to housewives in terms of making simple financial reports and developing promotions for local products by utilizing the latest technology. The participation of housewives who are MSME actors can support environmental sustainability to increase the economic independence of the community in Karya Jaya II Village through the green economy is very important